Adverse pregnancy outcomes associated with adenomyosis with uterine enlargement - Mochimaru, Aya; Aoki, Shigeru; Oba, Mari S.; Kurasawa, Kentaro; Takahashi, Tsuneo; Hirahara, Fumiki (The journal of obstetrics and gynaecology research, 2015)
Aim The aim of this study was to elucidate the risk of poor pregnancy outcomes in women with adenomyosis by comparing their outcomes to those of women without uterine abnormalities. Material and Methods The subjects were 36 women diagnosed with adenomyosis before pregnancy who were managed at a tertiary care center between January 2002 and December 2012. Our hospital database was retrospectively reviewed to identify pregnancy outcomes associated with adenomyosis. The control group consisted of 144 women without uterine abnormalities who gave birth during the same period and whose age at delivery was adjusted by applying propensity scores. Pregnancy outcomes were compared between the adenomyosis and control groups. The main outcomes were gestational age at delivery, preterm delivery, preterm premature rupture of membranes, fetal malpresentation, cesarean delivery, small‐for‐gestational age, 5‐min Apgar score < 7, umbilical arterial pH < 7.1, and neonatal intensive care unit admission. The data are presented as medians (range) or frequencies (percentage). Results The adenomyosis group had significantly higher rates of preterm delivery (41.7% vs 12.5%), preterm premature rupture of membranes (19.4% vs 4.2%), small‐for‐gestational age (33.3% vs 10.4%), fetal malpresentation (27.8% vs 8.3%), and cesarean delivery (58.3% vs 24.3%), as compared with the control group. No significant differences were observed in 5‐min Apgar score < 7 or umbilical arterial pH < 7.1 between the two groups. Conclusions Pregnancies in women with adenomyosis were associated with a higher preterm delivery rate and more frequent occurrences of fetal growth restriction and fetal malpresentation, such that both pregnancy and delivery outcomes were poor.